Pelatihan Perencanaan Karir Dalam Upaya Meningkatkan Kematangan Karir Pada Siswa Madrasah Aliyah (MA) - Syaifussalam, Muhammad Lathief; Wigati, Meilia; Wilantika, Rima; Hanifah, Raidah; Fertha, Fitria (STMIK Royal, 2024)
Madrasah Aliyah (MA) students. The method used in training is through lectures, discussions, assignments, questions and answers. The presenter delivers psychoeducation about careers to open up insight into the benefits and importance of careers for students, self-awareness to increase self-awareness, Johari window to increase knowledge about oneself, set the goals using the SMART method, reveal one's potential through SWOT analysis, and personality analysis through the RIASEC test to determine the suitability of personality with the desired career. Measurements were carried out twice. The first measurement (pre-test) is carried out before implementing the program to determine the initial conditions for student career decision-making. The second measurement (post-test) is carried out after students receive career training. Next, the results of the pre-test and post-test data were statistically analyzed using a paired-sample t-test using SPSS 23.0 for Windows. The results of the PKM activities carried out show that career planning training is able to increase the career maturity of MA students. Students' understanding of themselves will help them determine their career plans in accordance with their interests and talents.Keyword : career maturity; career training; students